Preparing Faculty for Utilization of Innovative Approaches in Digitalized Teaching and Learning Environments - Agalo, Joyce; Mafunga, Dennis (Machakos University, 2018)
The emergence of new information and communication technologies that can be used to enhance teaching and learning environments provide both an opportunity to transform delivery of education and a challenge in its adoption. With the proliferation of portable and adaptable technologies, it is currently possible to access educational content anywhere with internet connectivity. This has heightened the interest for online learning and most academic institutions now provide options for both face -to- face and electronic leaning. Hence the need arises to prepare faculty to adopt the emerging approaches in teaching as they integrate technology in the delivery of instruction. The learners also need orientation in order to adapt to the virtual and online learning environments. An important factor in the success of managing online instruction is the training of faculty before launching online courses and provision of support throughout the study. The emphasis placed on training of faculty for online instruction, will determine its success or failure. It is important to determine and address the needs related to online instruction appropriately. With the dynamic technological advances, it is critical that faculty are updated on new learning devices in order to provide learners with interactive, rich and engaging online content. There is need to rethink teaching and learning as we embrace innovative approaches such as utilization of e-learning platforms, social media, you-tube, open educational resources, initiating collaborations and partnerships with industry and educational institutions. Integration of information and communication technologies into teaching and learning offers significant potentials for higher education institutions resulting in transformations in delivery approaches and presentation of content. This paper is based on the experience of training and supporting faculty and students at institutions of higher learning. It explores innovative approaches that enhance instruction and highlights the challenges faced by faculty when transforming roles from face-to-face teaching to managing digitized learning environments. Keywords: E-Learning Technologies; Online Instruction; Digitized Teaching; Course Design
Keywords: E-Learning Technologies; Online Instruction; Digitized Teaching